"Get the f#∗k out of my way!" Exploring the cathartic effect of swear words in coping with driving anger. (July 2018) - Popuşoi, Simona A.; Havârneanu, Grigore M.; Havârneanu, Corneliu E.
Highlights: We identified three traffic situations in which drivers report swearing frequently. We measured the drivers' affective state before and after swearing. Swearing has a cathartic role for the driver when pedestrians cross illegally. Swearing leads to more positive affective valence. Swearing is a type of verbal aggression and a possible way to cope with anger. Abstract: Previous studies suggest that swearing is a prevalent expression of verbal aggression among drivers, but the role of swearing as a coping mechanism with anger remains unknown. The current article explored the cathartic role of swearing in situations when drivers experienced strong negative emotions. First we conducted a structured interview (N = 35) to identify the primary traffic situations when drivers regularly swear. In the second pre-study (N = 28) we examined the levels of negative and positive affect generated by these situations in order to identify the scenarios most likely to generate anger. The main study (N = 250) tested the cathartic role of swearing in these scenarios, by measuring its influence on the self-reported negative affective valence and level of physical activation. Results indicated three frequently swearing situations which are characterized by negative affect and high physical activation for the driver: (1) being forced to slow down by pedestrians who cross the road in illegal places; (2) being refused the legitimate right of way by another driver; and (3) traffic jams caused by cars which are stopped or parked illegally on the roadway. However, results showed that swearing had a cathartic role only in the first of these three situations. These findings suggested that swearing is not only an expression of verbal aggression towards another road user, but occasionally a way to cope with anger, which leads to better outcomes for the driver such as more positive affect and lower physical activation.